2011
DOI: 10.1016/j.mbs.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Bistable responses in bacterial genetic networks: Designs and dynamical consequences

Abstract: A key property of living cells is their ability to react to stimuli with specific biochemical responses. These responses can be understood through the dynamics of underlying biochemical and genetic networks. Evolutionary design principles have been well studied in networks that display graded responses, with a continuous relationship between input signal and system output. Alternatively, biochemical networks can exhibit bistable responses so that over a range of signals the network possesses two stable steady … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 142 publications
(202 reference statements)
3
67
0
Order By: Relevance
“…In many other organisms, the cell fate decision has been shown to be controlled by the ultrasensitive activation of the master regulator through positive feedback, resulting in a bistable response. Thus, two stable states of the responses correspond to two distinct cell fates (47)(48)(49)(50)(51)(52)(53). Surprisingly, despite the presence of positive feedback in the phosphorelay architecture, we have found that the phosphorelay response to KinA induction is graded and nonultrasensitive.…”
Section: Discussionmentioning
confidence: 72%
“…In many other organisms, the cell fate decision has been shown to be controlled by the ultrasensitive activation of the master regulator through positive feedback, resulting in a bistable response. Thus, two stable states of the responses correspond to two distinct cell fates (47)(48)(49)(50)(51)(52)(53). Surprisingly, despite the presence of positive feedback in the phosphorelay architecture, we have found that the phosphorelay response to KinA induction is graded and nonultrasensitive.…”
Section: Discussionmentioning
confidence: 72%
“…As in other fields of engineering, advances have been enabled by the use of small interchangeable modules that are 'functionally equivalent' from an input -output perspective [2]. Bistable circuits-which play a role in essential biological processes, including cell fate specification [3], cell cycle progression [4] and apoptosis [5]-make up a particularly large and diverse functionally equivalent set [6]. Effectively characterizing and comparing these biocircuits is crucial for determining which design is in some sense optimal for a particular context.…”
Section: Introductionmentioning
confidence: 99%
“…However, a binary or greatly delayed response is not likely preferred by all signaling systems; rather, a continuous well-defined output in relation to input signals allows cells to make accurate and prompt adjustments. It has been suggested that most TCSs tend to be monostable and the TCS autoregulatory architecture is distinct from conventional positive feedback loops due to the negative phosphatase activities of bifunctional HKs [6], [7], [14]. Constitutively expressed TCSs often complement the loss of autoregulated systems without causing apparent differences in steady-state outputs under laboratory conditions [7], [15][19].…”
Section: Introductionmentioning
confidence: 99%